The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/jcp.30375
|View full text |Cite
|
Sign up to set email alerts
|

The molecular structure and role of CCL2 (MCP‐1) and C‐C chemokine receptor CCR2 in skeletal biology and diseases

Abstract: Monocyte chemoattractant protein‐1, also called chemokine (C‐C motif) ligand 2 (CCL2) or small inducible cytokine A2, is an inflammatory mediator capable of recruiting monocytes, memory T cells, and dendritic cells. CCL2 is a member of the CC chemokine superfamily, which binds to its receptor, C‐C motif chemokine receptor‐2 (CCR2), for the induction of chemotactic activity and an increase of calcium influx. It exerts multiple effects on a variety of cells, including monocytes, macrophages, osteoclasts, basophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 93 publications
0
46
1
1
Order By: Relevance
“…IGF2 regulates cell proliferation, growth, migration, differentiation, and survival via its protein hormone [ 37 ]. CCL2 can recruit monocytes, memory T cells, and dendritic cells as part of the CC chemokine superfamily responsible for chemotactic activity and increases in calcium influx [ 38 ]. EMILIN1 regulates systemic blood pressure, as well as being part of the extracellular matrix [ 39 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…IGF2 regulates cell proliferation, growth, migration, differentiation, and survival via its protein hormone [ 37 ]. CCL2 can recruit monocytes, memory T cells, and dendritic cells as part of the CC chemokine superfamily responsible for chemotactic activity and increases in calcium influx [ 38 ]. EMILIN1 regulates systemic blood pressure, as well as being part of the extracellular matrix [ 39 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…4A ), which indicated that the activity of GSDMD was involved in the activation of innate and adaptive immunity in scleroderma. The heatmap summarized that the loss of GSDMD impaired the expression level of chemokines and its receptors including CXCL3, CXCL2, CCL2, CCL3, CCL4, CCL17 and CCR1, CCR2, CCR5, which can control the migratory patterns of immune cells such as the recruitment of leukocytes to infected or damaged tissue [ 18 ], regulate immune activation of T cells [ 19 ], and play an important role in autoimmune diseases [ 20 ]. CCL2 and CCL3 have previously been found to be elevated in SSc [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, transcription and expression of IL-1, CCL2 and TNF genes are initiated by MCP1P1 ( 76 ). Upon triggering of CCR2 by CCL2, a variety of intracellular G protein-mediated signaling gateways will be initiated, for instance JAK/STAT, PI3K/MAPKs and PI3K/Akt/ERK/NF-κB ( 77 ) ( Figure 2 ) . Activation of these signaling pathways results in the mobilization of multiple transcription factors and genes involved in cytokine production, cell growth and differentiation, cell survival, migration and apoptosis, angiogenesis and inflammation ( 62 , 78 , 79 ).…”
Section: Basic Information Of Ccl2-ccr2 Axismentioning
confidence: 99%